Projeto editorial para livros de baixa tiragem com encadernação artesanal - Araújo, Bernardo Ribeiro de (2011)
This work presents a brief look into the world’s and national publishing scene of today, analysing the better options and the difficulties that authors face while trying to publish their books. It is also analysed the proper methods used in each kind of project. Least, it’s described the practical side of the publishing process and the graphic design aspect of creating a book, from the first contact with the authors up to the finishing of the product.